Elementary School Students’ Likes and Dislikes about Outside, Inside and Meal/Snack Recess - Ken R Lodewyk; Lauren McNamara (Educational Considerations, 2025)
Studies on enjoyment of school recess rarely differentiate between gender or the indoor and outdoor settings (and especially not the eating portion of recess or lunch), so the aim of this study was to qualitatively increase understanding about what students specifically like and dislike about recess relative to gender and outside, inside, and meal/snack preferences. Participants were 386 students (203 girls and 183 boys) from grades 4 through 8 in seven Catholic elementary schools within one school district of southern Ontario, Canada. Participants completed an online survey during one of their scheduled classes, wherein they answered several open-ended questions. Two overarching themes emerged from the data, namely that social experiences are vital in shaping recess experiences and that students need opportunities to meaningfully and actively engage in recess. More specifically, for most students, positive social interactions might be compromised more during inside and meal/snack recess than outside recess. Students also generally valued more differentiated activity opportunities during recess, and 3.4% of girls and 5.5% of boys reported feeling unsafe from mean kids during outside recess. Finally, girls may be more susceptible to disliking many traditional outside recess contexts, whereas boys might be more susceptible than girls to being bored and frustrated during inside (and perhaps meal/snack) recess.
Keywords: indoors; outdoors; preferences; lunch; gender